Assessment of glucokinase regulatory protein rs1260326 gene variant polymorphism in the development of nonalcoholic fatty liver disease among Egyptian obese children. Issue 2 (April 2016) - Eladawy, Mohammed; Kamal, Tarek M.; Ibrahim, Khaled; Elbaz, Farida
Abstract : Background: Several gene variants have been identified so far by genome-wide association studies or by a candidate gene approach to be associated with fatty liver disease. Aim: The aim of the present study was to assess the prevalence of rs 1260326 of the glucokinase regulatory protein ( GCKR ) gene in nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis among a sample of obese Egyptian children. Patients and methods: This study included 100 obese children followed-up at the obesity clinic of Ain Shams University Children's Hospital and 50 healthy, nonobese children. Study candidates were further subclassified into three groups: group I – 50 obese children with 'no hepatomegaly' and normal liver enzymes; group II – 30 obese children with 'hepatomegaly' and normal liver enzymes; group III – 20 obese children with 'hepatomegaly and elevated liver enzymes' (nonalcoholic steatohepatitis); and group IV – 50 healthy, nonobese children matched for age and sex as a control group only for the genetic study. Epidemiological, clinical, and laboratory data were collected from the medical records of the first three groups. The GCKR gene variant rs1260326 was studied in patients with NAFLD (groups II and III) and the control group (group IV). Results: NAFLD patients (groups II and III) included 29 males and 21 females with a mean age of 8.5±4.4 years and mean duration of obesity of 4.2±2 years. There was a highly significant statistical difference between groups II, III, and I regarding duration of obesity, weight, BMI, hip circumference, waist circumference, and lipid profile. The most prevalent GCKR genotype among NAFLD was CC (52%), whereas controls showed more heterozygosity for the CT allele. The most frequently segregated allele among patients was C (69%) followed by T (31%). Conclusion: The most prevalent polymorphic genotype of rs 1260326 within the GCKR among Egyptian obese children with NAFLD was CC, and the most prevalent allele among them was the C allele.